P134 Sleep Laboratory contact in adults commencing CPAP: a post-hoc analysis of the AHEAD trial. (9th November 2022) - Webster, K; Ellender, C
Abstract: Background: CPAP used for >4hrs/night effectively treats obstructive sleep apnoea(OSA), however CPAP adherence is often poor. A randomised control trial from our department demonstrated improved CPAP adherence at 12 months in patients receiving video education (VE), compared with standard of care education (SOCE) at CPAP commencement. This follow-on study aimed to evaluate 12-month clinic utilisation of patients in the AHEAD trial, hypothesizing that increased unscheduled contact by patients in the intervention arm may contribute to improved CPAP adherence. Methods: Post-hoc analysis of data from the AHEAD trial was performed. The AHEAD trial included 195 patients recruited from a large trial protocol and randomised to either SOCE or SOCE+VE. Demographics including age, gender, education level and socioeconomic indices were collected. CPAP usage was assessed at 2-, 6-, and 12-months post randomisation. Adequate adherence was defined as usage >4hours/night. Further data on number of scheduled and unscheduled visits at 12-months post randomisation was collected. The primary outcome was number of unscheduled visits in intervention vs control arm. Progress to date: Study groups were well-matched at baseline. The proportion with adequate CPAP usage at 12mths was higher in the VE group (33, 33% versus 48, 50% p=0.01). Preliminary analysis suggests there are no significant differences in number of unscheduled visits at 12-month follow up between SOCE vs SOCE+VE (mean0.29 vs 0.43 p=0.18). Further analysis will investigate predetermined subgroups – including low educational level / socioeconomic status. Intended outcome and impact: This study will inform strategies to improve CPAP adherence in patients with OSA.